On the statistics of the discharged wastewater quality indicators - Anatoly P. Lepikhin; Tatyana N. Sintsova (Водное хозяйство России: проблемы, технологии, управление)
For the construction of correct, objective schemes for the regulation of technogenic impacts on water bodies, the nature of the statistical functions of the distribution of chemical indicators of the quality of wastewater discharged is of fundamental importance. In connection with this, the mechanisms of the formation of these distribution functions in the discharged wastewater of various industrial enterprises are considered.